Frequency of toxocara infection in children attended by the health public service of Maringá, south Brazil Freqüência de infecção por Toxocara em crianças atendidas em serviço público de Maringá, sul do Brasil - Márcia L. Paludo; Dina L.M. Falavigna; Guita R. Elefant; Mônica L. Gomes; Magda L.M. Baggio; Luciano B. Amadei; Ana Lúcia Falavigna-Guilherme (Revista do Instituto de Medicina Tropical de São Paulo, 2007)
The lack of specific laboratorial diagnosis methods and precise symptoms makes the toxocariasis a neglected disease in Public Health Services. This study aims to determine the frequency of Toxocara spp. infection in children attended by the Health Public Service of Hospital Municipal de Maringá, South Brazil. To evaluate the association of epidemiological and clinical data, an observational and cross-section study was carried out. From 14,690 attended children/year aged from seven month to 12 years old, 450 serum samples were randomly collected from September/2004 to September/2005. A questionnaire was used to evaluate epidemiological, clinical and hematological data. An ELISA using Toxocara canis larval excretory-secretory products as antigen detected 130 (28.8%) positive sera, mainly between children from seven month to five years old (p = 0.0016). Significant correlation was observed between positive serology for Toxocara, and frequent playing in sandbox at school or daycare center (p = 0.011) and the presence of a cat at home (p = 0.056). From the families, 50% were dog owners which exposed soil backyards. Eosinophilia (p = 0.776), and signs and symptoms analyzed (fever p = 0.992, pneumonia p = 0.289, cold-like symptoms p = 0.277, cough p = 0.783, gastrointestinal problems p = 0.877, migraine p = 0.979, abdominal pain p = 0.965, joint pain p = 0.686 and skin rash p = 0.105) could not be related to the presence of anti-Toxocara antibodies. Therefore, two asthmatics children showed titles of 1:10,240 and accentuated eosinophilia (p = 0.0001). The authors emphasize the needs of prevention activities. A falta de métodos de diagnóstico laboratorial específico e sintomas específicos fazem da toxocaríase uma doença negligenciada nos serviços públicos de saúde. Este estudo teve por objetivo determinar a freqüência de infecção por Toxocara spp. em crianças atendidas no serviço público do Hospital Municipal de Maringá, sul do Brasil, e avaliar a associação com dados epidemiológicos e clínicos, em estudo observacional ...